The Influence of Gene-Gene and Gene-Environment Interactions on the Risk of Asbestosis - Franko, A. (Hindawi Publishing Corporation, 2013)
This study investigated the influence of gene-gene and gene-environment interactions on the risk of developing asbestosis. The study comprised 262 cases with asbestosis and 265 controls with no asbestos-related disease previously studied for MnSOD, ECSOD, CAT, GSTT1, GSTM1, GSTP1, and iNOS polymorphisms. Data on cumulative asbestos and smoking were available for all subjects. To assess gene-gene and gene-environmental interactions, logistic regression was used. The associations between MnSOD Ala −9Val polymorphism and the risk of asbestosis and between iNOS genotypes and asbestosis were modified by CAT –262 C > T polymorphism (P = 0.038; P = 0.031). A strong interaction was found between GSTM1-null polymorphism and smoking (P = 0.007), iNOS (CCTTT)(n) polymorphism and smoking (P = 0.054), and between iNOS (CCTTT)(n) polymorphism and cumulative asbestos exposure (P = 0.037). The findings of this study suggest that the interactions between different genotypes, genotypes and smoking, and between genotypes and asbestos exposure have an important influence on the development of asbestosis and should be seriously considered in future research on occupational/environmental asbestos-related diseases.